Songket Rajang – The Thread of Heritage (Short Video) - Awang Arshad, A.H; Rafee, Y.M; Abol Hassan, M.Z; Jussem, S.W (Old Kuching Smart Heritage (OKSHe), 2020)
This short video with a duration of 6 minutes and 28 seconds is a summary of the Songket Rajang production process. The filming was done in in the Kampung Rajang, Tanjung Manis, Sarawak and funded under the Nusantara Chair grant (F03 / NRC / 1655/2018). This video has won second place in the Old Kuching Smart Heritage (OKSHe) video competition and the video can be viewed via https://www.youtube.com/watch?v=bEMJ8cXJRxs